Infertile Women Below the Age of 40 Have Similar Anti-Müllerian Hormone Levels and Antral Follicle Count Compared With Women of the Same Age With No History of Infertility. Issue 8 (August 2016) - Hvidman, H. W.; Bentzen, J. G.; Thuesen, L. L.; Lauritsen, M. P.; Forman, J. L.; Loft, A.; Pinborg, A.; Andersen, A. Nyboe
Abstract : (Abstracted from Hum Reprod 2016;31(5):1034–1045) The study investigates the extent to which poor response to ovarian stimulation in assisted reproductive technologies is associated with a lower ovarian reserve, estimated by serum concentrations of anti-müllerian hormone (AMH) and antral follicle count (AFC), in infertile patients when compared with women of same age with no history of infertility. A prospective cohort study of 382 infertile patients referred for fertility treatment at The Fertility Clinic, Rigshospitalet, at Copenhagen University Hospital between September 2011 and October 2013 were compared with a control group of 350 nonusers of hormonal contraception with no history of infertility between August 2008 and February 2010.